Knowledge and Attitude Regarding Emergency Contraception Among Nursing Personnel - Thapa, Basanta (Journal of Chitwan Medical College, 2013)
Emergency contraception plays vital role reducing maternal mortality substantially and improves maternal health by avoiding unwanted pregnancy and unsafe abortion. The objective of this study was to find out the knowledge and attitude of nursing personnel regarding emergency contraception. On an average, 96.33% of nursing personnel had knowledge on general information of Emergency Contraception (EC), 88.78% had knowledge about intrauterine contraceptive device as EC, 66.1% had knowledge on general information of emergency contraceptive pills, 65.5% had knowledge on its dosage and administration and only 59.05% had knowledge on its side effects and their management. On an average, 72.83% of them had knowledge on EC as a whole. More than three- fourth (78.18%) of them had positive attitude towards EC. When comparing nurses’ knowledge between educational qualifications, training on EC, duration of experience and between in-service training on family planning counseling, there was statistically no significant difference on knowledge between these variables. When studying the correlation between nurses’ knowledge and attitude regarding EC, it was found to be moderately correlated (r = 0.537). Based on the findings, it is concluded that on an average majority of nursing personnel tend to have knowledge on emergency contraception as a whole. Majority of them are likely to have positive attitude towards EC. Knowledge regarding emergency contraception is not related to different variables. Nurses’ knowledge and attitude regarding emergency contraception have positive correlation. Journal of Chitwan Medical College 2013; 3(1): 46-50 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8466